LITERARY REVIEW OF IBRAHIM YUSUPOV'S WORK (The Conference Hub, 2025)
Hero of Uzbekistan Ibrahim Yusupov was not only a poet but also one of the outstanding literary critics who notably distinguished himself in Karakalpak literary criticism from the 1950s-1960s. Zh. Yesenov notes the genre uniqueness of the poet's works in the field of literary criticism, stating: "I. Yusupov has many literary-critical articles in the form of reviews, portrait criticism, prefaces, and essays" [1, 33].